Cost Evaluation On The Effect Of Adopting Different Shear Wall Arrangements For Rectangular Office Building Under Seismic Design - Tan, Hong Yang (Universiti Sains Malaysia, 2022)
Penang Island is located in the low seismic zone. However, due to the past earthquakes incidents that caused structural damage to a few buildings to the non-seismic design, it is vital to consider the involvement of seismic design (EC8) onto the construction of building that only complied to the non-seismic design (EC2). This study is carried out with the aim to evaluate the effect of different structural systems towards the concrete volume and reinforcement bar quantity, the total cost, and the net floor area of buildings under seismic design. Three types of reinforced concrete building frame of 25 storeys, 30 storeys and 35 storeys with the incorporation of different shear wall arrangements were designed and analysed using ETABS software package. The buildings were designed using EC2 and MS1553:2002 for gravity load and wind load, respectively. On the other hand, EC8 was used for seismic design with the reference Peak Ground Acceleration value of 0.05 g (low ductility class) and soil type D as it represents the seismicity conditions in Penang Island. The results showed that the total concrete volume and reinforcement bar cost for the building models with respect to building heights and different shear wall arrangements decreased in the range of 6.2%-16.1% for non-seismic design and 1.1%-10.6% for seismic design. This finding is associated to the fact that the incorporation of shear wall increases the building resistant towards lateral load. On the other hand, the net floor area was found to be insignificantly increased (1%-2%) when the incorporation of different shear wall arrangements is adopted. It can be concluded that incorporation of seismic design for Penang case increases the total material cost, although the additional cost can be considered as relatively low (less than 7%). On the contrary, the incorporation of additional shear wall reduces the total cost (1%-11%) and particularly true for all building heights with seismic design. In addition, the incorporation of additional shear wall slightly increases the net floor area and particularly true in the case of non-seismic and seismic design.